Carbon sequestration in biomass of immature-rubber, banana and pineapple intercropping system - Mohamadu Boyie Jalloh; Jamal Bin Talib; Wan Sulaiman Wan Harun; Mohd Fauzi Ramlan; Christopher B.S. Teh (Malaysian Society of Soil Science (MSSS), 2007)
Carbon sequestration in soil or the net removal of C02 from the atmosphere into long-lived soil carbon (C) pools has received a lot of research attention but less so for plant biomass C pools. However, C sequestration in plant biomass is considerably huge especially in forest ecologies. The potential of agricultural cropping systems (soils and crops), particularly crops, acting as sinks for the greenhouse gas C02 is huge, thereby reducing C02 levels in the atmosphere. In the case of the crops, C02 from the atmosphere is fixed into the crops through photosynthesis. In the soil, C is fixed in the form of organic matter in the soil from the litter of plant materials. Agriculture also acts as a source of C02 emissions through biomass burning, deforestation, tillage, fossil fuels burning and land degradation.